Digital Justice in the Contentious Administrative Jurisdiction: The Quickness Principle Based on ICTs as an Instrument for Judicial Decongestion in Colombia - Carmen Cecilia Diz Muñoz; Carlos Andrés Sánchez Peña; Daniela María Orozco Poveda; Yassith Yaneth Muskus Tobias (Opinión Jurídica)
This paper analyzes the application of the quickness principle and its effectiveness around modernity, referring to the use of information technologies in contentious administrative processes, thanks to the modification of law 1437 (2011) through law 2080 (2021). This reform of the Code of Administrative Procedure and Administrative Litigation (2011) carries out a significant development of the quickness principle through its different precepts, including portals, web, and technological systems. The ICTs use is a necessity due to the pandemic caused by Covid 19, which has rethought the rhythm of life of all citizens of the Nation and how administration justice. For this paper, we use a descriptive methodology to fulfill the proposed objective, which allows the analysis and description of the factors and premises to conclude, using secondary and tertiary sources, such as laws, scientific documents, research papers, and other documents complying with the above. In conclusion, the relation between the quickness principle and the ICT allows them to safeguard their rights and that there are no unjustified delays due to the parties’ lack of information tools or access quickly and safely. It is a positive change that does not present many discussions because it is a step toward the modernization of judicial processes in administrative matters, which is also obviously very open so that they can be carried out more efficiently by public servants and public servants—Entities, which will be adapted to the different situations that arise.